2013
DOI: 10.1596/1813-9450-6646
|View full text |Cite
|
Sign up to set email alerts
|

Regulation, Renegotiation and Capital Structure: Theory and Evidence from Latin American Transport Concessions

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 16 publications
1
11
0
Order By: Relevance
“…This is a similar result to Spiegel and Spulber (1994), Moore et al (2014) and other articles who show that regualted firms will issue more debt relative to equity when faced with the threat of government expropriation of equity. Since there is a lower amount of equity invested, investors will incentivize the manager to induce less effort, and costs will be higher in expectation.…”
Section: Limited Government Commitmentsupporting
confidence: 86%
“…This is a similar result to Spiegel and Spulber (1994), Moore et al (2014) and other articles who show that regualted firms will issue more debt relative to equity when faced with the threat of government expropriation of equity. Since there is a lower amount of equity invested, investors will incentivize the manager to induce less effort, and costs will be higher in expectation.…”
Section: Limited Government Commitmentsupporting
confidence: 86%
“…Milena, Salinas, Ochoa, and Molina (2012) presents a review of empirical studies in Latin American countries that analyse the empirical verification of the hierarchical order theory. Moore et al (2013) in a World Bank study showed how the regulation of the capital structure in concessionaires transport firms reduces the level of leverage in the companies and they use more their own resources.…”
Section: Introductionmentioning
confidence: 99%
“…The result is shown in We can see that the average asset-liability ratio of GEM enterprises in 2012, 2013 and 2014 is 0.2402, 0.2676 and 0.2676 respectively, and the average issuance ratio is 0.2158, 0.2423, 0.2497, the trend of increasing year by year, the average long-term debt ratio of 0.0244, 0.0253, 0.0395, also showed a year-on-year trend. You can find these data, although little change, but it is also growing year by year, just in line with the slow development of the GEM technology-based enterprises [9]. This also shows that the capital structure of the GEM technology companies in the debt financing ratio gradually increased, companies gradually give up the concept of equity financing, more attempts to debt financing [10].…”
Section: Gem Characteristics Of Science and Technology Enterprisesmentioning
confidence: 74%